2021
DOI: 10.1007/s10518-021-01170-5
|View full text |Cite
|
Sign up to set email alerts
|

In-plane lateral cyclic behaviour of lime-mortar and clay-brick masonry walls in dry and wet conditions

Abstract: This paper presents an experimental investigation into the structural and material response of ambient-dry and wet clay-brick/lime-mortar masonry elements. In addition to cyclic tests on four large-scale masonry walls subjected to lateral in-plane displacement and co-existing compressive gravity load, the study also includes complementary tests on square masonry panels under diagonal compression and cylindrical masonry cores in compression. After describing the specimen details, wetting method and testing arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…The failure occurs as a result of a combination of normal and shear stress on the wall [23]. In this case, the principal tensile strength in the cross-section of the wall exceeds the diagonal tensile strength of the masonry wall [2,24]. Diagonal cracks can be the stepped and straight modes in the masonry wall [25].…”
Section: Unreinforced Brick Masonry Wall (Bw Wall)mentioning
confidence: 99%
See 1 more Smart Citation
“…The failure occurs as a result of a combination of normal and shear stress on the wall [23]. In this case, the principal tensile strength in the cross-section of the wall exceeds the diagonal tensile strength of the masonry wall [2,24]. Diagonal cracks can be the stepped and straight modes in the masonry wall [25].…”
Section: Unreinforced Brick Masonry Wall (Bw Wall)mentioning
confidence: 99%
“…The Timoshenko beam theory assumes the lateral displacement obtained from the shear and flexural strength to define the initial stiffness [24,27]. The ratio between the shear and elastic modulus (G/E) is 0.05 for the 0.2 N/mm 2 pre-compression stress by experiment in Table 3.…”
Section: Formulamentioning
confidence: 99%
“…1a, the specimens were positioned and loaded through V-shaped supports. External transducers were used for secondary measurements alongside the displacement recordings provided by the machine, coupled with detailed data from a Digital Image Correlation (DIC) system (Elghazouli et al 2021).…”
Section: Diagonal Panelsmentioning
confidence: 99%
“…In terms of the crack kinematics, similar behaviour was observed during tests on both air-dry and wet specimens. Close inspection of the results showed that the moisture reduced both the stiffness and the specimen strength, albeit with different extents as a function of mortar strengths (Elghazouli et al 2021). The response of dry panels was generally characterised by loss of bond at a horizontal bed joint at the centre of the panel at around 80-90% of the peak capacity Pu.…”
Section: Diagonal Panelsmentioning
confidence: 99%
“…Half of the specimens were kept in laboratory conditions (T = 24-30 °C, RH = 30-50%), whilst the remaining specimens were in wet conditions by full submersion in water for 48h. To assess the compressive strength of the masonry, cylinders made of two vertical brick cores, with a mortar joint of about 10 mm in between, were extracted from undamaged masonry walls (Elghazouli et al 2021). The cylinders had a diameter d = 69 mm and height of around h = 145 mm, representing an aspect ratio h/d ≈ 2.10.…”
Section: Compression Testsmentioning
confidence: 99%